2012
DOI: 10.1111/j.1468-1331.2012.03662.x
|View full text |Cite
|
Sign up to set email alerts
|

Screening of the FUS gene in familial and sporadic amyotrophic lateral sclerosis patients of Chinese origin

Abstract: The frequency of FUS mutations is approximately 1.0% in our SOD1-, ANG-, TARDBP-mutation-negative sporadic ALS cohort and similar to that reported in previous studies from Asia in our familial ALS cohort. [Correction added on 31 May 2012, after first online publication: the gene FUS- was changed to ANG-]. Our findings provide an overview of the occurrence of FUS mutations in Chinese sporadic and familial ALS cases and highlight the importance of screening for FUS mutations in ALS patients of Chinese origin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
2

Year Published

2013
2013
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 35 publications
3
10
2
Order By: Relevance
“…Mutations in SOD1 were present in 20.0% of fALS patients and 1.9% of sALS patients, which is consistent with previous studies in western populations8, and indicates that SOD1 mutations play a key role in the pathology of ALS patients from different ethnicities. In addition, the frequency of FUS mutation was approximately 13.3% in fALS patients, which is consistent with reports from several other populations11121314, but is higher than the frequencies found in Catalan (8%)15, German (2.4–6.9%)1617, Italian (4.4%)12, and Belgian (2.9%)18 populations. This difference may be due to small sample sizes and the differing ethnicities of fALS patients.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Mutations in SOD1 were present in 20.0% of fALS patients and 1.9% of sALS patients, which is consistent with previous studies in western populations8, and indicates that SOD1 mutations play a key role in the pathology of ALS patients from different ethnicities. In addition, the frequency of FUS mutation was approximately 13.3% in fALS patients, which is consistent with reports from several other populations11121314, but is higher than the frequencies found in Catalan (8%)15, German (2.4–6.9%)1617, Italian (4.4%)12, and Belgian (2.9%)18 populations. This difference may be due to small sample sizes and the differing ethnicities of fALS patients.…”
Section: Discussionsupporting
confidence: 91%
“…Although FUS mutations were not found in sALS patients, this is probably due to both the selective detection of exons in mutational hotspot regions and the use of small sample sizes. Zou ZY reported that FUS mutations could be present in approximately 1.0% of northern Chinese sALS patients, which is similar to the 1.6% mutation frequency found in Korean patients and the 1.25% mutation frequency found Italian patients12141920. With regards to the frequency of TARDBP mutation, it appears that the frequency of TARDBP mutations in Caucasian populations (Italy: 2.7%; France and Quebec: 4.5%) was higher than that in Asian populations21222324.…”
Section: Discussionmentioning
confidence: 61%
“…In contrast, our patient showed early and predominant bulbar symptoms and a paresis of the neck muscles leading to a dropped-head syndrome as the first symptom. In earlier reports the mutation p.Arg521Leu was identified in familial ALS patients (Millecamps et al, 2010;Yan et al, 2010;Zou et al, 2012). Unfortunately, no parental DNA was available for segregation analysis in our patient.…”
Section: A C C E P T E D Accepted Manuscriptcontrasting
confidence: 53%
“…In patient 12, the FUS mutation p.Arg521Leu was identified. This alteration was described to be associated with a distinct clinical phenotype characterized by a predominant upper limb weakness emerging in the 3 rd and 4 th decade with minimum evidence of bulbar and upper motor neuron involvement (Zou et al, 2012). In contrast, our patient showed early and predominant bulbar symptoms and a paresis of the neck muscles leading to a dropped-head syndrome as the first symptom.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 85%
“…The first two reports suggested that FUS mutations might only be associated with FALS [Kwiatkowski et al, ; Vance et al, ]. However, several recent reports identified FUS mutations in SALS patients, including the most common variants p.R521C and p.R521H (Table ) [Belzil et al, ; Blair et al, ; Broustal et al, ; Chiò et al, ; Corrado et al, ; Drepper et al, ; Groen et al, ; Kwiatkowski et al, ; Lai et al, ; Millecamps et al, ; Rademakers et al, ; Sproviero et al, ; Suzuki et al, ; Syriani et al, ; Ticozzi et al, ; Tsai et al, ; van Blitterswijk et al, ; Vance et al, ; Van Damme et al, ; Van Langenhove et al, ; Yamamoto‐Watanabe et al, ; Yan et al, ; Zou et al, ].…”
Section: Fus Mutations In Alsmentioning
confidence: 99%